Healthcare-seeking delays and associated factors among immigrant patients with acute ischaemic stroke in Shenzhen: a retrospective observational study - Qingshi Zhao; Changyu Li; Zongbi Wu; Youli Jiang; Yanfeng Li (BMJ Open)
Objective To examine healthcare-seeking delays among immigrant patients with acute ischaemic stroke (AIS), identifying key factors contributing to these delays and proposing evidence-based interventions for policy formulation and research.Design A retrospective observational study analysing healthcare-seeking behaviours and delay times among immigrant patients with AIS treated at the Department of Neurology, Longhua District People’s Hospital, Shenzhen, from December 2021 to October 2023. The study included 1356 patients with AIS, all part of the immigrant population as defined by Shenzhen Statistical Yearbook criteria. The study investigated sociodemographic, clinical data and stroke-specific scales (modified Rankin Scale, National Institutes of Health Stroke Scale, Glasgow Coma Scale) to identify factors influencing delays.Setting The study was conducted in Shenzhen, a city characterised by a significant immigrant population, providing insights applicable to urban regions with similar demographics.Results Of the 1356 patients studied, 82.6% (n=1120) experienced healthcare-seeking delays, with a median delay of 12.67 hours (IQR: 3.5–28.8). Factors associated with prolonged delays included lack of stroke awareness (92.96% delay rate), low educational attainment, self-transportation to the hospital (adjusted OR (aOR): 2.36, 95% CI: 1.57 to 3.54) and wake-up strokes (aOR: 4.37, 95% CI: 2.28 to 8.36). Conversely, factors associated with shorter delays included cardioembolic strokes (aOR: 0.50, 95% CI: 0.28 to 0.90) and atrial fibrillation (aOR: 0.45, 95% CI: 0.23 to 0.89). Delay rates were significantly lower among patients referred by emergency medical services compared with those self-transporting. These findings highlight the influence of clinical, socioeconomic and demographic factors on delays in seeking care.Conclusion Healthcare-seeking delays in stroke care among immigrants, shaped by awareness, socioeconomic and clinical factors, necessitate urgent educational, policy and healthcare reforms. Enhancing early symptom recognition and promoting emergency service utilisation are essential for improving access to care and outcomes in this vulnerable group.